Systematic review of diarrhea duration and severity in children and adults in low- and middle-income countries - Lamberti, Laura M; Fischer Walker, Christa L; Black, Robert E (BMC public health, 2012)
Background Diarrhea is a leading cause of morbidity and mortality globally; yet the overall burden of diarrhea in terms of duration and severity has not been quantified. As improvements in treatment lead to decreases in diarrhea mortality, it is important to understand the substantial impact of diarrhea morbidity on disability among children and adults worldwide. Methods We conducted a systematic review to generate estimates of duration and severity outcomes for individuals 0-59 mos, 5-15 yrs, and ≥ 16 yrs, and for 3 severity indexes: mild, moderate, and severe. Results We estimate that among children under-five, 64.8% of diarrheal episodes are mild, 34.7% are moderate, and 0.5% are severe. On average, mild episodes last 4.3 days, and severe episodes last 8.4 days and cause dehydration in 84.6% of cases. We estimate that among older children and adults, 95% of episodes are mild; 4.95% are moderate; and 0.05% are severe. Among individuals ≥ 16 yrs, severe episodes typically last 2.6 days and cause dehydration in 92.8% of cases. Conclusions Moderate and severe episodes constitute a substantial portion of the total envelope of diarrhea among children under-five (35.2%; about 588 million episodes). Among older children and adults, moderate and severe episodes account for a much smaller proportion of the total envelope of diarrhea (5%), but the absolute number of such episodes is noteworthy (about 21.5 million episodes among individuals ≥ 16 yrs). Hence, the global burden of diarrhea consists of significant morbidity, extending beyond episodes progressing to death.